2001
DOI: 10.1073/pnas.221466798
|View full text |Cite
|
Sign up to set email alerts
|

Gambicin: A novel immune responsive antimicrobial peptide from the malaria vector Anopheles gambiae

Abstract: A novel mosquito antimicrobial peptide, gambicin, and the corresponding gene were isolated in parallel through differential display-PCR, an expressed sequence tag (EST) project, and characterization of an antimicrobial activity in a mosquito cell line by reverse-phase chromatography. The 616-bp gambicin ORF encodes an 81-residue protein that is processed and secreted as a 61-aa mature peptide containing eight cysteines engaged in four disulfide bridges. Gambicin lacks sequence homology with other known protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
136
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 42 publications
(75 reference statements)
6
136
0
2
Order By: Relevance
“…gambiae (Richman et al, 1997;Vizioli et al, 2001;Nikou et al, 2003), we found that expression of this gene fluctuated across the array of developmental stages we tested ( Supplementary Fig. 2).…”
Section: Data Analysesmentioning
confidence: 86%
“…gambiae (Richman et al, 1997;Vizioli et al, 2001;Nikou et al, 2003), we found that expression of this gene fluctuated across the array of developmental stages we tested ( Supplementary Fig. 2).…”
Section: Data Analysesmentioning
confidence: 86%
“…Upregulation of AMPs during infection have been reported [49,50]. Transferrin is a defence molecule which has been shown to be up-regulated in Cx.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that ectopic overexpression of CEC1 drastically reduces susceptibility of mosquitoes to Plasmodium (33). Other REL2-regulated proteins that might explain the observed phenotype are Gambicin (GAM1), another AMP with antiparasitic activity in vitro (34), and LRIM1, a key antagonist of ookinete-tooocyst development (13).…”
Section: Discussionmentioning
confidence: 99%